Pengaruh Pendekatan Deep Learning Menggunakan Mnemonic Terhadap Kemampuan Berpikir Kritis Kelas VII Pada Materi Klasifikasi Makhluk Hidup di SMP Negeri 46 Samarinda - Adinda Pramuditha; Elsje Theodora Maasawet; Vandalita Maria Magdalena Rambitan; Nelda Anasthasia Serena (UNIB Press, 2026)
The inefficient implementation of learning approach and method can make student participant less active and leads to lack of critical thinking skills. This study aims to determine the effect of the deep learning approach using mnemonics on the critical thinking skills of seventh-grade students regarding the classification of living organisms at SMP Negeri 46 Samarinda. This study employed a quasi-experimental research design with a non-equivalent control group design. Sampling was conducted using purposive sampling, with a sample size of 25 students each for the experimental and control classes. The data analysis techniques used are N-Gain test and the Independent Sample T-Test. The results of the data analysis showed that the N-Gain score for critical thinking skills in the experimental class, with an average of 0.74, fell into the high category, while that of the control class, at 0.60, fell into the moderate category. The hypothesis results showed a significance value (2-tailed) of 0.000 for critical thinking skills, where this significance value (2-tailed) was < 0.05 so it can be concluded that there is an effect of the deep learning approach using mnemonics on the critical thinking skills of seventh-grade students regarding the classification of living organisms at SMP Negeri 46 Samarinda.